Moška poklica Slovencev ob morju - Volpi Lisjak, Bruno (Etnolog. Nova vrsta (Ljubljana), 2002)
The article presents two now extinct occupations which used to be carried out by Slovene fishermen from the environs of Trieste. Šavornanti provided ballastto unloaded merchant sailing ships until the 1920s. Kolnarji were experienced fishermen, trained to spot the arrival of major shoals of tuna fish from viewpoints above the sea and warn the other fishermen in the harbour.
Keywords: Slovenci v Italiji; ribištvo; ribiči; poklici; man; moški; šavornanti; kolnarji